Case report: Anti-CARPVIII autoantibody-associated mixed dementia - Hansen, Niels; Teegen, Bianca; Hirschel, Sina; Wiltfang, Jens; Schott, Björn H.; Malchow, Berend; Claudia, Bartels (Frontiers in Psychiatry, 2023)
Background Anti-carbonic anhydrase-related protein VIII (CARPVIII) is reported to be associated with paraneoplastic cerebellar degeneration. Our case extends the spectrum of anti-CARPVIII-associated disease to severe cognitive impairment. Methods We present the case of a 75-year-old woman who presented to our Department of Psychiatry and Psychotherapy with a dementia syndrome. The diagnostic approach included magnetic resonance imaging (MRI), cerebrospinal fluid analysis (CSF) analysis involving autoantibody determination, and neuropsychological examination. Results Neuropsychological examination revealed severe cognitive impairment meeting the criteria for dementia. MRI showed evidence of moderate cerebral microangiopathy. CSF analysis revealed mild pleocytosis, and serum analysis revealed anti-CARP VIII autoantibodies. Based on the dementia syndrome entailing signs of CNS inflammation such as pleocytosis and the repeated detection of anti-CARPVIII autoantibodies in serum, we diagnosed autoimmune dementia as a component of mixed dementia with additional vascular dementia components. Conclusions Our finding adds severe cognitive impairment to the spectrum of anti-CARPVIII-associated disease. However, detecting anti-CARPVIII antibodies may also be an incidental finding in conjunction with typical mixed dementia. Further studies are needed to evaluate the relevance of these clinical findings.